Assessment of the probability of entry of Rift Valley fever virus into the EU through active or passive movement of vectors. Issue 2 (14th February 2020) - Van Bortel, Wim; Petric, Dusan; Ibáñez Justicia, Adolfo; Wint, Willy; Krit, Meryam; Mariën, Joachim; Vanslembrouck, Adwine; Braks, Marieta
Abstract : The overall aim of this scientific report is the assessment of the probability of entry of Rift Valley fever virus (RVFV) into the European Union (EU) through active or passive movement of vectors. Two different import pathways were considered in this report, i.e. import through flights and import via cargo on ships. The import through road transport, eggs or immature stages, and wind was not considered in this report as thought to be zero or negligible. In total 39 potential RVFV vectors were identified based on our review. Of the 39 identified potential vectors of RVFV, the five highest ranked based on their distribution in the African at‐risk countries, their potential role as vector, and their behavioural and ecological traits influencing the risk of transportation were: Anopheles pharoensis, Aedes aegypti, Mansonia uniformis, Aedes mcintoshi, and Culex quinquefasciatus . Four of these species were also detected in airports or airplanes in the EU. The estimated probability of entry of RVFV infected mosquito vectors into the EU through the passive movement of mosquito vectors by flights is medium for the Netherlands, France, Germany and Italy. These countries are heavily connected through direct flights from the 14 at‐risk countries in Africa. A low risk of RVFV import was estimated for Spain, Poland, Belgium and Austria and for 16 countries the risk was zero. Overall the risk of RVFV import through ship‐cargo was zero for most of the EU Member States and low for the Netherlands, Spain, Germany and Belgium.